Pentingnya Etika dan Moral dalam Pendidikan - Devi Ayu Lestari; Wanda Kholisah; M. Rifqi Januar Supriyanto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
In the colorful labyrinth of education, morals and ethics act as a compass guiding individuals through the right path. Education is not just about acquiring knowledge but also about shaping a strong character and good values. Morality and ethics serve as a solid foundation in building individuals of integrity and responsibility. At every turn of education, individuals are shaped into figures who are not only academically intelligent but also have admirable personalities.